A bilayer conducting polymer structure for planar perovskite solar cells with over 1,400 hours operational stability at elevated temperatures - Zhao, Yicheng; Heumueller, Thomas; Zhang, Jiyun; Luo, Junsheng; Kasian, Olga; Langner, Stefan; Kupfer, Christian; Liu, Bowen; Zhong, Yu; Elia, Jack; Osvet, Andres; Wu, Jianchang; et al. (Nature Energy, 2021)
The long-term stability of perovskite solar cells remains a challenge. Both the perovskite layer and the device architecture need to endure long-term operation. Here we first use a self-constructed high-throughput screening platform to find perovskite compositions stable under heat and light. Then, we use the most stable perovskite composition to investigate the stability of contact layers in solar cells. We report on the thermal degradation mechanism of transition metal oxide contact (for example, Ta-WOx/NiOx) and propose a bilayer structure consisting of acid-doped polymer stacked on dopant-free polymer as an alternative. The dopant-free polymer provides an acid barrier between the perovskite and the acid-doped polymer. The bilayer structure exhibits stable ohmic contact at elevated temperatures and buffers iodine vapours. The unencapsulated device based on the bilayer contact (with a MgF2 capping layer) retains 99% of its peak efficiency after 1,450 h of continuous operation at 65 degrees C in a N-2 atmosphere under metal-halide lamps. The device also shows negligible hysteresis during the entire ageing period.
CRIS-Team WoS Importer:2021-12-24

An Innovative Anode Interface Combination for Perovskite Solar Cells with Improved Efficiency, Stability, and Reproducibility - Meng, Wei; Xu, Junyi; Dong, Lirong; Zhang, Jiyun; Xie, Zhiqiang; Luo, Junsheng; Zhao, Baolin; Zhang, Kaicheng; Osvet, Andres; Heumüller, Thomas; Forberich, Karen; Halik, Marcus; et al. (Solar RRL, 2022)
Rational design and engineering of top interface layers with combined properties of effective passivation, high thermal- and photo-stability are effective methods to advance the commercialization of perovskite photovoltaics. Here, an innovative anode interface combination is developed based on alcohol-dispersed poly (3-hexylthiophene-2,5-diyl) (P3HT) nanoparticles as the hole transport material and chlorobenzene-dissolved trioctylphosphine oxide (TO PO) as the passivation agent. It is shown that instead of the commonly used 2D passivation ligands, TOPO-passivated perovskite films exhibit greatly improved thermal stability. Furthermore, the passivation contributes to an enhanced carrier lifetime and reduced surface trap density, yielding an improvement in the quasi-fermi-level splitting of 57 meV. To maintain surface passivation during solution processing of further layers, it is necessary to develop a hole transport layer that can be processed from orthogonal solvents. P3HT nanoparticles formulated in alcoholic media fully meet this requirement, clearly benefitting from their high vertical conductivity and extremely low contact resistance with carbon electrodes. Based on this configuration, device efficiency of up to 18.4% is demonstrated for perovskite solar cells with fully solution-processed carbon electrodes, along with significantly improved device stability and reproducibility.
CRIS-Team WoS Importer:2022-06-17

Doping of Mesoscopic Charge Extraction Layers Enables the Design of Long-Time Stable Organic Solar Cells - Xu, Junyi; Luo, Junsheng; Gubanov, Kirill; Barabash, Anastasia; Fink, Rainer; Heumüller, Thomas; Brabec, Christoph (ACS Energy Letters, 2024)
Realizing efficient and stable organic solar cells (OSCs) via all-solution processing requires the design of tailored charge extraction interfaces. Herein, we demonstrate a substantially different interface concept for OSC that is based on a low-temperature processed mesoscopic hole transporting layer (HTL) derived from partially covered organic nanoparticles (NPs) in the n-i-p structure. The mesoscopic interface is further doped in a second coating step with an organic salt dopant, BCF-Li. The interactions among the dopant, the solvent for sequential doping, and the semiconductor layer are surprisingly complex. The mesoscopic interface is necessary to evenly wet the semiconductor and prevent the aggregation of the dopant. At the same time, the sequential process reduces the excess acceptor at the interface. Both processes together are necessary to generate an efficiently doped interface for low-Ohmic-charge extraction and stable contacts. Devices with fully solution-processed mesoscopic interfaces show a superb shelf lifetime of over 22000 h without encapsulation and a long-term operational stability under 1 sun illumination for 2000 h (T80). Flexible devices bypass 1000 bending cycles with negligible degradation. Mesoscopic doped interfaces are demonstrated as an alternative to PEDOT:PSS as well as PEDOT related interface concepts for nonfullerene acceptors (NFA) in the n-i-p architecture.
CRIS-Team Scopus Importer:2024-01-12

Exploring the Steric Hindrance of Alkylammonium Cations in the Structural Reconfiguration of Quasi-2D Perovskite Materials Using a High-throughput Experimental Platform - Zhang, Jiyun; Wu, Jianchang; Langner, Stefan; Zhao, Baolin; Xie, Zhiqiang; Hauch, Jens; Afify, Hany A.; Barabash, Anastasia; Luo, Junsheng; Sytnyk, Mykhailo; Meng, Wei; Zhang, Kaicheng; et al. (Advanced Functional Materials, 2022)
Reduced-dimensional (2D or quasi-2D) perovskites have recently attracted considerable interest due to their superior long-term stability. The nature of the intercalating cations plays a key role in determining the physicochemical properties and stability of the quasi-2D perovskites. Here, the thermal stability of a series of 2D Ruddlesden−Popper (RP) perovskites is studied using seven types of intercalating cations with increasing linear carbon-chain length from ethylammonium (EA) to n-dodecylammonium (DA) through a high-throughput platform. The results show that long-chain cations in quasi-2D perovskite films lead to strong steric hindrance between adjacent perovskite domains, thus suppressing Ostwald ripening during the thermal-aging process. For short-chain cations, increased-dimensional phase redistribution during the aging period is observed, which can benefit a concomitant regeneration of the 3D/3D-like perovskite phases. The impact of steric hindrance on structural reconfiguration and the subsequent phase redistribution in quasi-2D perovskites are systematically characterized by UV–vis absorption spectra, photoluminescence spectra, and X-ray diffraction patterns. Due to the steric hindrance effect, an optimal chain length is found to maximize film stability by balancing the water/oxygen resistance and increased-dimensional phase redistribution. This work provides new insight into the thermal stability of quasi-2D perovskites.
CRIS-Team Scopus Importer:2022-09-02
Keywords: 2D perovskite materials; high-throughput platform; stability performance; steric hindrance; steric structure and reconfiguration

Impact of 2D Ligands on Lattice Strain and Energy Losses in Narrow-Bandgap Lead–Tin Perovskite Solar Cells - Zhang, Kaicheng; Vincze, Andrej; Metwalli, Ezzeldin; Zhang, Jiyun; Liu, Chao; Meng, Wei; Zhang, Boxue; Tian, Jingjing; Heumüller, Thomas; Xie, Zhiqiang; Luo, Junsheng; Osvet, Andres; et al. (Advanced Functional Materials, 2023)
Mixed lead and tin (Pb/Sn) hybrid perovskites exhibit a great potential in fabricating all-perovskite tandem devices due to their easily tunable bandgaps. However, the energy deficit and instability in Pb/Sn perovskite solar cells (PSCs) constrain their practical applications, which renders defect passivation engineering indispensable to develop highly efficient and long-term stable PSCs. Herein, the mechanisms of strain tailoring and defect passivation in Pb/Sn PSCs by 2D ligands are investigated. The 2D ligands include electroneutral cations with long alkyl chain (LAC), iodates with relatively short alkyl chain (SAC) and their mixtures. This study reveals that LAC ligands facilitate the relaxation of tensile strain in perovskite films while SAC ligands cause strain buildup. By mixing LAC/SAC ligands, tensile strain in perovskite films can be balanced which improves solar cell performance. PSCs with admixed β-guanidinopropionic acid (GUA)/phenethylammonium iodide (PEAI) exhibit enhanced open circuit voltage and fill factor, which is attributed to reduced nonradiative recombination losses in the bulk and at the interfaces. Furthermore, the operational stability of PSCs is slightly improved by the mixed 2D ligands. This work reveals the mechanisms of 2D ligands in strain tailoring and defect passivation toward efficient and stable narrow-bandgap PSCs.
CRIS-Team Scopus Importer:2023-07-07
Keywords: 2D ligand passivation; energy losses; lead/tin perovskite solar cells; stability; strain tailoring

Integrated System Built for Small-Molecule Semiconductors via High-Throughput Approaches - Wu, Jianchang; Zhang, Jiyun; Hu, Manman; Reiser, Patrick; Torresi, Luca; Friederich, Pascal; Lahn, Leopold; Kasian, Olga; Guldi, Dirk Michael; Perez-Ojeda Rodriguez, Maria Eugenia; Barabash, Anastasia; Rocha Ortiz, Juan Sebastian; et al. (Journal of the American Chemical Society, 2023)
High-throughput synthesis of solution-processable structurally variable small-molecule semiconductors is both an opportunity and a challenge. A large number of diverse molecules provide a possibility for quick material discovery and machine learning based on experimental data. However, the diversity of the molecular structure leads to the complexity of molecular properties, such as solubility, polarity, and crystallinity, which poses great challenges to solution processing and purification. Here, we first report an integrated system for the high-throughput synthesis, purification, and characterization of molecules with a large variety. Based on the principle “Like dissolves like,” we combine theoretical calculations and a robotic platform to accelerate the purification of those molecules. With this platform, a material library containing 125 molecules and their optical-electronic properties was built within a timeframe of weeks. More importantly, the high repeatability of recrystallization we design is a reliable approach to further upgrading and industrial production.<br

Inverse design workflow discovers hole-transport materials tailored for perovskite solar cells - Wu, Jianchang; Torresi, Luca; Hu, Manman; Reiser, Patrick; Zhang, Jiyun; Rocha-Ortiz, Juan S.; Wang, Luyao; Xie, Zhiqiang; Zhang, Kaicheng; Park, Byung-Wook; Barabash, Anastasia; Zhao, Yicheng; et al. (Science, 2024)
The inverse design of tailored organic molecules for specific optoelectronic devices of high complexity holds an enormous potential but has not yet been realized. Current models rely on large data sets that generally do not exist for specialized research fields. We demonstrate a closed-loop workflow that combines high-throughput synthesis of organic semiconductors to create large datasets and Bayesian optimization to discover new hole-transporting materials with tailored properties for solar cell applications. The predictive models were based on molecular descriptors that allowed us to link the structure of these materials to their performance. A series of high-performance molecules were identified from minimal suggestions and achieved up to 26.2% (certified 25.9%) power conversion efficiency in perovskite solar cell
CRIS-Team Scopus Importer:2025-02-04

Printing High-Quality Formanidinum Lead Triiodide Films: Understanding the Critical Role of α-Phase Nucleation Before Thermal Annealing - Qiu, Shudi; Dong, Lirong; Jang, Dongju; Yang, Fu; García Cerrillo, José; Li, Chaohui; Xie, Zhiqiang; Luo, Junsheng; Guo, Fei; Distler, Andreas; Du, Tian; Brabec, Christoph; et al. (Advanced Energy Materials, 2024)
Upscaling the coating of formamidinium lead triiodide (FAPbI3) thin film is essential to realizing full printing and thereby roll-to-roll production of perovskite photovoltaics. However, thin-film FAPbI3 processed from antisolvent-free, printing methods suffer from undesirable degradation to the non-photoactive phase, particularly in ambient processing conditions. Here, the most critical stage in thin-film processing is identified as the gas-quenching treatment of the as-cast wet film. It is crucial to achieve both the nucleation of α-phase nanocrystals and their sufficient growth at room temperature, which are indispensable for templating the growth of a highly crystalline and stable α-FAPbI3 film during subsequent thermal annealing. The gas-quenching-treated film without these α-phase nanocrystals can only be converted to meta-stable α-FAPbI3 by thermal annealing. By precisely identifying the spontaneous doping of cesium ion (Cs+) as a key factor in triggering α-FAPbI3 nucleation and the role of chloride ion (Cl−) in enhancing nanocrystal growth, a generalized mechanism for additive engineering for the precursor ink is theorized. The identified mechanism translates to a power conversion efficiency of 19.36% for fully printed carbon-electrode solar cells, 16.23% for carbon-electrode minimodules, and excellent operational stability, showing the promising potential of this proposed fabrication route in the upscaling of perovskite photovoltaics.
CRIS-Team Scopus Importer:2024-10-25
Keywords: carbon-electrode; cesium ion; FAPbI; nucleation; perovskite photovoltaics

Revealing Degradation Mechanisms in 3D/2D Perovskite Solar Cells under Photothermal Accelerated Ageing - Peng, Zijian; Vincze, Andrej; Streller, Fabian; Le Corre, Vincent Marc; Zhang, Kaicheng; Li, Chaohui; Tian, Jingjing; Liu, Chao; Luo, Junsheng; Zhao, Yicheng; Späth, Andreas; Fink, Rainer; et al. (Energy and Environmental Science, 2024)
Three-dimensional/two-dimensional (3D/2D) heterojunctions in perovskite solar cells exhibit excellent optoelectronic properties and enhanced stability under mild ageing conditions. However, their performance degrades drastically under harsh ageing conditions. This study reveals the intrinsic instability of mono-ammonium based 2D perovskites (2D-mono) under photo-thermal ageing, which decompose into PbI2 and metallic lead (Pb0). The structural collapse promotes vacancy formation and facilitates iodide migration to the anode. As a result, it triggers a redox reaction that reduces the transport layer’s mobility and doping concentration, leading to a significant increase in series resistance. Compared to mono-ammonium-2D structure, di-ammonium-2D (2D-di) based interfaces demonstrate superior structural stability and effectively block iodide migration into the transporting layer. However, blocking-induced uneven iodide distribution leads to interstitial defect formation in the 3D layer, exacerbating non-radiative recombination. To address it, we propose a strategical method by incorporating 2D-di in the 3D bulk instead of on the top surface, which effectively confines mobile ions within the grain and suppresses cation phase segregation. This optimization yields stable perovskite solar cells with an extrapolated operational T80 lifetime exceeding 560 hours under harsh conditions (85°C and 2-sun illumination